Analysis of combustion instability of hydrogen fueled scramjet combustor on high-speed OH-PLIF measurements and dynamic mode decomposition. (28th April 2020) - Peng, Jiangbo; Cao, Zhen; Yu, Xin; Yang, Shunhua; Yu, Yang; Ren, Hongyu; Ma, Yufei; Zhang, Shunping; Chen, Shuang; Zhao, Yanhui
Abstract: This paper investigated the combustion instability of spanwise positions in a hydrogen fueled scramjet combustor with a cavity flame holder. High-speed OH-PLIF technique was performed on a direct-connect supersonic combustion facility, and dynamic mode decomposition (DMD) as postprocessing. Combustion instability was investigated by characterizing the dominant frequencies and growth factors. By changing the equivalence ratio of hydrogen, the peak frequencies of scramjet mode and ramjet mode were obtained. Scramjet mode tended to have small oscillation at 150–200 Hz reflected by negative growth factors due to the stable flame structure. At ram-to-scram transition, oscillations at 80–120 Hz were remarkably enhanced due to the positive growth factors. In ramjet mode, the large differences of frequency characteristics in spanwise positions were observed. The dominant DMD modes near the cavity wall appeared to have negative growth factors leading to a stable flame with small oscillations. Besides, the characteristics of frequency-shift were affected by the positions of injector. Highlights: High-speed OH-PLIF measurements and DMD analysis are performed. Combustion instability is investigated by characterizing the dominant frequencies and growth factors. The frequency characteristics of spanwise positions are significantly different. The cavity wall appears to have good combustion stability.